PERAN MEDIA DAN STRATEGI KOMUNIKASI PEMBERDAYAAN DALAM MENGELOLA KONFLIK SOSIAL: TINJAUAN LITERATUR KOMUNIKASI PEMBANGUNAN - Sukri M; Sarmiati Sarmiati (Jurnal Psikotes, 2026)
This paper examines the role of communication in managing social conflict from the perspective of development communication with a focus on empowerment. Social conflict is often viewed as a failure of development; however, this study argues that conflict also reflects inequalities in communication processes and access to media. The objective of this study is to analyze how media and empowerment-based communication strategies contribute to conflict management within development contexts. Using a narrative literature review with a systematic approach, this study analyzes scholarly articles published over the last 10–15 years from national and international journals. Thematic synthesis is employed to identify key patterns related to media roles, participatory communication, and empowerment strategies. The findings indicate that media can function both as a catalyst and a mediator of conflict, depending on communication practices, while empowerment-oriented strategies such as community participation, dialogue, and media literacy play a crucial role in reducing conflict escalation. The study concludes that integrating empowerment principles into development communication enhances conflict management effectiveness.